Algebra 2 (Houghton Mifflin Harrourt Publishing Company, 2012)
This book introduce assessment and intervention system for adaptive instruction and individualized RtI. Robust On Core ExamView® Assessment Suite for Common Core Assessment preparation. Math Practices emphasized in student lessons and correlated in Teacher’s Editions